2020
DOI: 10.1186/s12891-020-03748-7
|View full text |Cite
|
Sign up to set email alerts
|

Is kinesiophobia a predictor of early functional performance after total hip replacement? A prospective prognostic cohort study

Abstract: Background Considerable attention has been paid to the role of kinesiophobia with respect to knee prosthesis but it has not yet been studied as a prognostic factor of short-term functional performance following total hip replacement. The main purpose of the present study is to examine the possible predictors of early functional performance of patients undergoing total primary hip arthroplasty, including demographics as age, sex and body mass index, preoperative functional ability, type of anaesthesia, level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
2
16
2
Order By: Relevance
“…However, the prevalence of kinesophobia were similar across the socio-demographic characteristics of the patients and that includes age, gender, level of education, BMI level, and occupation. These reports are not consistent with the study of Morri et al [12], based on their accounts, age, sex, and BMI were the significant factors associated with kinesophobia. Similarly, Manali et al [11] accounted that age was observed to have a positive correlation with TSK score which coincided with the study done in Italy but differed from our study.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…However, the prevalence of kinesophobia were similar across the socio-demographic characteristics of the patients and that includes age, gender, level of education, BMI level, and occupation. These reports are not consistent with the study of Morri et al [12], based on their accounts, age, sex, and BMI were the significant factors associated with kinesophobia. Similarly, Manali et al [11] accounted that age was observed to have a positive correlation with TSK score which coincided with the study done in Italy but differed from our study.…”
Section: Discussioncontrasting
confidence: 91%
“…Their findings showed that there was a strong positive correlation between pain and the TSK score. However, in a study by Morri et al [12], they documented that there was no significant correlation between numerical rating scale score and kinesiophobia score postoperatively which were not in accordance with our report.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The influence of sociodemographic factors on the occurrence of kinesiophobia was also noted by Morri et al As in the authors' own research, female sex may affect a higher level of perioperative anxiety. The researchers also included age and body weight as unfavorable factors influencing kinesiophobia [19].…”
Section: Discussionmentioning
confidence: 99%